Keterlibatan Penggunaan Media Sosial pada Interaksi Sosial di Kalangan Gen Z - Hana Apriyanti; Ira Safaat Aeni; Reva Sila Kinaya; Nasywa Hasna Nabilla; April Laksana; Lika Mulki Latief (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
The development of digital technology, especially social media, has brought significant changes in the way of interacting and communicating among the younger generation, especially Gen Z. Gen Z, who was born between 1997 and 2012, grew up in the digital era where social media became the main platform for connecting, sharing information, and building community. This study aims to explore the influence of social media on social interaction among Gen Z, with a focus on the positive and negative impacts arising from the use of social media in their daily lives. Social media allows Gen Z to connect with peers, form identities, and participate in various virtual communities. However, while it provides an opportunity to expand social networks, research shows that social media can also reduce the quality of deeper social relationships. Interactions that occur in cyberspace tend to be more superficial compared to face-to-face communication, which can interfere with the development of social skills and empathy. In addition, social comparisons that often occur on social media also affect mental health, causing feelings of anxiety, loneliness, and dissatisfaction with oneself.